Redox modulation of plant developmental regulators from the class I TCP transcription factor family - Viola, Ivana Lorena (2013)
TEOSINTE BRANCHED1-CYCLOIDEA-PROLIFERATING CELL FACTOR1 (TCP) transcription factors participate in plant developmental processes associated with cell proliferation and growth. Most members of class I, one of the two classes that compose the family, have a conserved cysteine at position 20 (Cys-20) of the TCP DNA-binding and dimerization domain. We show that Arabidopsis (Arabidopsis thaliana) class I proteins with Cys-20 are sensitive to redox conditions, since their DNAbinding activity is inhibited after incubation with the oxidants diamide, oxidized glutathione, or hydrogen peroxide or with nitric oxide-producing agents. Inhibition can be reversed by treatment with the reductants dithiothreitol or reduced glutathione or by incubation with the thioredoxin/thioredoxin reductase system. Mutation of Cys-20 in the class I protein TCP15 abolished its redox sensitivity. Under oxidizing conditions, covalently linked dimers were formed, suggesting that inactivation is associated with the formation of intermolecular disulfide bonds. Inhibition of class I TCP protein activity was also observed in vivo, in yeast (Saccharomyces cerevisiae) cells expressing TCP proteins and in plants after treatment with redox agents. This inhibition was correlated with modifications in the expression of the downstream CUC1 gene in plants. Modeling studies indicated that Cys-20 is located at the dimer interface near the DNA-binding surface. This places this residue in the correct orientation for intermolecular disulfide bond formation and explains the sensitivity of DNA binding to the oxidation of Cys-20. The redox properties of Cys-20 and the observed effects of cellular redox agents both in vitro and in vivo suggest that class I TCP protein action is under redox control in plants.